2011
DOI: 10.1021/ml200091q
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent Dual PPARα Agonists/CB1 Ligands

Abstract: This letter describes the synthesis and in vitro and in vivo evaluation of dual ligands targeting the cannabinoid and peroxisome proliferator-activated receptors (PPAR). These compounds were obtained from fusing the pharmacophores of fibrates and the diarylpyrazole rimonabant, a cannabinoid receptor antagonist. They are the first examples of dual compounds with nanomolar affinity for both PPARα and cannabinoid receptors. Besides, lead compound 2 proved to be CB1 selective. Unexpectedly, the phenol intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…While our initial studies were ongoing, McGuinness et al (26) reported that fenofibrate was a near‐full agonist compared with CP55940 in a HEK293‐CB 2 cell line using the PathHunter β‐arrestin recruitment assay, with an EC 50 value of 55 nM, in keeping with our results for fenofibrate in competitive radio‐ligand and GTPγS binding assays. In addition, Perez‐Fernandez et al (27) described a series of compounds combining pharmacophores of fenofibrate and rimonabant with nanomolar affinity for both CB 1 and PPAR‐α, although as these compounds were selective antagonists at the CB 1 receptor in the mouse vas deferens bioassay, it is likely that their CB1 effects were mediated via the rimonabant pharmacophore.…”
Section: Discussionmentioning
confidence: 99%
“…While our initial studies were ongoing, McGuinness et al (26) reported that fenofibrate was a near‐full agonist compared with CP55940 in a HEK293‐CB 2 cell line using the PathHunter β‐arrestin recruitment assay, with an EC 50 value of 55 nM, in keeping with our results for fenofibrate in competitive radio‐ligand and GTPγS binding assays. In addition, Perez‐Fernandez et al (27) described a series of compounds combining pharmacophores of fenofibrate and rimonabant with nanomolar affinity for both CB 1 and PPAR‐α, although as these compounds were selective antagonists at the CB 1 receptor in the mouse vas deferens bioassay, it is likely that their CB1 effects were mediated via the rimonabant pharmacophore.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the development of new drugs with dual activity as ligands for CB 1 and PPAR-α has been reported in recent years ( Alvarado et al . , 2008 ; Pérez-Fernández et al, 2011 ). Recently, we have synthesized and characterized a series of compounds derived from fatty acids conjugated with 3,4-methylenedioxymethamphetamine metabolites as anti-obesity drugs ( Almeida et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to obtain dual ligands targeting CB 1 R and PPARα, the diarylpyrazole core of the CB 1 R antagonist/inverse agonist SR141716A (Rimonabant, Figure 1) was fused to the phenoxypropanoate pharmacophore of the fibrates (fenofibrate, PPARα agonist, Figure 1), obtaining the so-called rimonabant fibrates [52]. The most potent compound of this series, 2 (Figure 1), exhibited nanomolar activity as a PPARα agonist in luciferase reporter gene assays and a CB 1 R antagonist in mouse vas deferens contractile response assays.…”
Section: Cb 1 R-pparαmentioning
confidence: 99%